Key microRNAs and target genes involved in regulating maturation in Lilium - Yao Chen; Mengna Zhao; Xiaoshan Wang; Jinteng Cui; Wei Ge; Kezhong Zhang (Ornamental Plant Research, 2022)
Lilium is an ornamental bulb with a long juvenile stage, making its cultivation under natural conditions lengthy and costly. SQUAMOSA promoter-binding protein-like (SPL) transcription factors are related to plant growth and development, including phase transition. However, their role in phase transition in Lilium is not known. To explore the molecular mechanisms associated with the phase transition in Lilium, bulbs of Lilium Oriental Trumpet 'Robina' were treated with lowered temperature to induce phase transition, and the small RNA and degradome were sequenced. A total of 161 miRNAs were identified as targets. Twenty-nine known miRNAs were differentially expressed, including 16 up-regulated miRNAs and 13 down-regulated miRNAs. Lbr-miR156a was significantly down-regulated, and the target genes of Lbr-miR156a were identified as LbrSPL3 and LbrSPL16.Phylogenetic analysis showed that LbrSPL3 and LbrSPL16 had high homology with other plant SPLs. Subcellular localization and transcriptional activation experiments confirmed that LbrSPL3 and LbrSPL16 were mainly located in the nucleus and had transcriptional activity. The in situ hybridization results showed that the expression of LbrSPL3 and LbrSPL16 was increased following low-temperature treatment. Functional verification experiments of Arabidopsis transgenic plants showed that the overexpression of LbrSPL3 and LbrSPL16 could promote plant phase change, while the overexpression of Lbr-miR156a could inhibit this process. These results help elucidate the mechanism of phase transition regulation in Lilium and provide a reference for breeding research in other bulbous flowers.